Perkembangan Literatur Hadis di Indonesia Abad Dua Puluh - Syaikh Abdillah (Diroyah : Jurnal Studi Ilmu Hadis, 2016)
Search efforts in the hadith and hadith experts say Indonesia can be said  not done systematically, not even adequate. It could be thought to be caused by several things. Firstly, the fact that the study of hadith moreover Hadith expert in Islamic studies is not as intense as others, such as al-Qur'an, fiqh, morals and so on. Second, the study of hadith can be said to be growing very slowly, especially when seen from the fact that the scholars Nusantara had written in tradition since the 17th century. However, as shown later, these writings are not developed further. Study hadith after it stagnated almost one and a half centuries. For this reason, the attention of the observer to the study of Hadith in Indonesia is still lacking. Even if there are observers who are concerned, attention is still partial and not comprehensive. This article will try to review the development of the study of Hadith in Indonesia in the twentieth century that belbatkan several works written by scholars of hadith or tradition can be said observers in the archipelago. Whether it works or original manuscripts speak Arabic and also there are some works that are adaptations of the work of other